The prodigal church : restoring Catholic tradition in an age of deception - McGinley, Brandon (Manchester Sophia institute press, 2020)
"A vision for renewing the Church in America: in the Church itself, the parish, the family, and the community"--
Includes bibliographical references.
Keywords: Catholic Church -- United States -- History -- 21st century; Church renewal -- Catholic Church